2012
DOI: 10.1080/09540121.2011.648602
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and avoidance in treating patients living with HIV/AIDS (PLWHA) among service providers in China

Abstract: This study aims to investigate health care providers’ empathy levels and its association with avoidance in providing service to patients living with HIV/AIDS (PLWHA) in China. A total of 1760 health service providers were randomly sampled from 40 county hospitals in two provinces of China. Using a self-administered questionnaire, participants’ demographic characteristics, work history, empathy level, and avoidance attitudes toward PLWHA were collected in a cross-sectional survey. Empathy was higher among parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Researchers who investigate multicomponent stigma-reduction programs (e.g., Li et al, 2013) may also incorporate the game-based experiential workshop as an interpersonal or affective component and test its additional contribution. Finally, our findings echoed the importance of promoting empathy, which was highlighted in other HIV stigma-reduction studies (e.g., Larson-Presswalla et al, 1995;Lin et al, 2012). More research is needed to elucidate the role of empathy in the effectiveness of the game-based experiential approach.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Researchers who investigate multicomponent stigma-reduction programs (e.g., Li et al, 2013) may also incorporate the game-based experiential workshop as an interpersonal or affective component and test its additional contribution. Finally, our findings echoed the importance of promoting empathy, which was highlighted in other HIV stigma-reduction studies (e.g., Larson-Presswalla et al, 1995;Lin et al, 2012). More research is needed to elucidate the role of empathy in the effectiveness of the game-based experiential approach.…”
Section: Discussionsupporting
confidence: 80%
“…More specifically, promoting an empathic perspective has been associated with more positive attitudes toward people living with HIV (PLHIV; Batson et al, 1997;Larson-Presswalla, Rose, & Cornett, 1995;Tarrant & Hadert, 2010). In China, health-care workers with a higher empathic level toward PLHIV reported less avoidance in treating them (Lin, Li, Wan, Wu, & Yan, 2012). Recognizing the power of an empathic perspective, the present study tested a HIV stigma-reduction intervention that focused on increasing sensitivity to the feelings of PLHIV through experiential games followed by group discussion.…”
mentioning
confidence: 97%
“…These beliefs persist even among (presumably better informed) Chinese health care providers, who exhibit generally low levels of support for PLHIV (2527) . Stigma contributes to these attitudes, as some providers reported feeling stigma and shame as a result of being associated HIV patients (26) , although providers with increased empathy had reduced avoidance of PLHIV, which improved the quality of their care (28) .…”
Section: Introductionmentioning
confidence: 99%
“…33,41,66,71,[83][84][85][86][87] In fact, Lin and colleagues, in their study among service providers in China, found that more empathetic attitudes were negatively related to avoidance attitudes. 88 We therefore suggest that interventions with health care providers seek to induce empathy by creating an awareness of those behaviors reflecting unintended instrumental stigma (e.g., use of differential precautions, labelling of files) and the impact of such behaviors on PLWH. 34 Empathy can also be cultivated by creating opportunities for contact between PLWH and health care providers, either directly or vicariously (e.g., through digital testimonials).…”
Section: Discussionmentioning
confidence: 99%